2017
DOI: 10.1093/jtm/taw088
|View full text |Cite
|
Sign up to set email alerts
|

Mountain medical kits: epidemiology-based recommendations and analysis of medical supplies carried by mountain climbers in Colorado

Abstract: : Mountain climbing epidemiology and current clinical guidelines suggest that a basic mountain medical kit should include items for body substance isolation, materials for immobilization, pain medications, wound care supplies, and medications for gastrointestinal upset and flu-like illness. The medical kits of Colorado mountain climbers varied considerable and often lacked essential items such as medical gloves. This suggests a need for increased guidance. Similar methodology could be used to inform medical ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…This suggests the need for improved guidelines. Brandenburg and Locke suggest that a similar methodology should be applied in relation to other mountain regions where there is limited formal healthcare (Brandenburg and Locke, 2017). The results of the research by B. Soulé, B. Lefèvre and E. Boutroy showed that mountain accidents mainly involve three types of activity: hiking, climbing and skiing (regardless of whether they resulted in death or injury) (Soulé, Lefèvre, and Boutroy, 2017).…”
Section: Scientific Research In the Area Of Terrestrial Rescuementioning
confidence: 99%
“…This suggests the need for improved guidelines. Brandenburg and Locke suggest that a similar methodology should be applied in relation to other mountain regions where there is limited formal healthcare (Brandenburg and Locke, 2017). The results of the research by B. Soulé, B. Lefèvre and E. Boutroy showed that mountain accidents mainly involve three types of activity: hiking, climbing and skiing (regardless of whether they resulted in death or injury) (Soulé, Lefèvre, and Boutroy, 2017).…”
Section: Scientific Research In the Area Of Terrestrial Rescuementioning
confidence: 99%
“…1 Overcrowding and poor sanitation, often found in high mountain camps, also play a role in certain instances. 1 The frequency of soft tissue injuries in mountainous recreation (11–23% of total incidents 19 ) from skin punctures, lacerations, and abrasions provide constant potential nidi for infection. Finally, those participating in wilderness outings, such as mountaineering, endure prolonged physical exertion coupled with inadequate sleep, further compromising host response.…”
Section: Bacteria: Staphylococcus Streptococcus and Yersiniamentioning
confidence: 99%
“…Elsensohn et al [5] concluded that there is no overview or recommendations on the material and medical equipment needed to treat victims in the mountain. This is partly due to elements such as national legislation, funding, lack of training in first aid, lack of knowledge of the most recurrent medical emergencies, or the characteristics of the environment (difficult terrain, adverse weather conditions, and inhospitable access) [5, 8]. It is therefore imperative that mountain sports technicians are highly self-sufficient, both in their technical field and in the areas of safety rescue areas, with adequate training, material, and equipment [8].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, priority should be given to items that are effective in treating probable incidents, such as basic life support equipment [9, 10], bandages and compresses, and blood pressure and temperature gauges. In addition, factors such as the terrain elevation, the season of the year, the experience of the mountain sports coaches, local laws, and the characteristics of the practitioners (technical, physical, and psychological) must be taken into account when preparing the medical kit [8]. It should also be noted that the training standards for the use and maintenance of medical equipment should be applied in the context of mountain sports [11, 12].…”
Section: Introductionmentioning
confidence: 99%